Healthy habits and mental health of undergraduates in non-health related careers - García-Pérez, Laura; Zamorano, Silvia; Rojas-Cepero, Iago; Miras-Moreno, Sergio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The university population is one of the most likely to adopt risky health behaviors. For this reason, a cross-sectional study was carried out with 184 university students in Granada. The aim was to determine the level of adherence to the Mediterranean diet, the level of physical activity, and the mental health of the quality of Life. Validated questionnaires were used: IPAQ-SF, KIDMED and SF-36. The main results were that most university students did not adhere to a quality diet, but did meet the minimum recommended physical activity. Additionally, university students with higher physical activity scores had a better diet and a better level of mental health. Therefore, it is a need to educate and train students in healthy habits. To this end, university programs should be created to encourage the student population to be physically active and take greater care of their diet.